Information security in an e-learning environment - Kritzinger, E. (2006)
In the last few years the education environment underwent a paradigm shift due to the rapid growth in technology. This growth made it possible for the education environment to utilize electronic services to enhance their education methods. It is, however, vital that all education environments (traditional or new ones) ensure that all resources (lectures, students and information) are properly protected against any possible security threats. This paper identifies technical and procedural (non-technical) information security countermeasures that could enhance the security of information within the education environments